Epimedium brevicornum Maxim. Extract exhibits pigmentation by melanin biosynthesis and melanosome biogenesis/transfer - Hong, Chen; Yang, Lili; Zhang, Yifan; Li, Yiming; Wu, Huali (Frontiers in Pharmacology, 2022)
Epimedium brevicornum Maxim. (Epimedii Folium) is a traditional medicine widely utilized in China for sexual dysfunction and osteoporosis treatment. Recently, studies have reported that Epimedium flavonoid icariin displayed hair growth and melanogenic ability by targeting tyrosinase activity. Nevertheless, icariin hydrolysate icariside II and icaritin cause depigmentation due to their tyrosinase inhibition. These pigment functional discrepancies from Epimedium constituents arouse our great interest. Then, this study focused on the pigmentation effects of Epimedii Folium extract (EFE) on melanin synthesis and melanosome biogenesis/transfer, and further identified the bioactive constituents. First, in in vitro systemic studies, we discovered that the potent melanogenic and repigmented effects of EFE were dependent on concentration and amount of time in multi-melanocytes, normal human skin tissue, and vitiligo perilesional areas. In vivo, EFE exhibited repigmented effect on two kinds of depigmented models of N-phenylthiourea-induced zebrafish and hydroquinone-induced mice. Mechanistically, EFE strongly promoted tyrosinase activity and upregulated the protein expression of tyrosinase families which finally contribute to melanin biosynthesis by activating the MAPK/ERK1/2 signal pathway. In addition, EFE effectively increased melanosome number, accelerated melanosome maturity and cytoplasmic transport through the growth/extension of melanocyte dendrites, and induced melanosome transfer from melanocyte to keratinocyte for pigmentation. The six main flavonoid ingredients were identified among EFE. Compared to others, epimedin B (EB) was confirmed as a high-content, low-toxicity, and effective melanogenic compound in EFE. Taking all these together, this study systematically demonstrates the potential pigmentation effect of Epimedium brevicornum Maxim., and clarifies its related molecular mechanisms and melanogenesis basis. These results give additional insight into Epimedium herb pharmacology and may provide a novel therapy basis for hypopigmentation disorders.